Determinants of disclosure and non-disclosure of HIV-positive status, by pregnant women in rural South Africa. Issue 1 (1st January 2018) - Ramlagan, Shandir; Matseke, Gladys; Rodriguez, Violeta J.; Jones, Deborah L.; Peltzer, Karl; Ruiter, Robert A.C.; Sifunda, Sibusiso
ABSTRACT: Disclosure of HIV status remains one of the major challenges to the effectiveness of the prevention of mother to child transmission of HIV in rural areas in South Africa. This study aimed at assessing the determinants of HIV status disclosure among HIV infected pregnant women who have disclosed their HIV status to someone, as well as among those who have disclosed to their partners. Cross-sectional data was collected from 673 HIV sero-positive pregnant women receiving antenatal care services at 12 Community Health Centers in Mpumalanga province. Results indicated that over two-thirds (72.1%) disclosed their status to someone, while just over half (58.4%) disclosed to their partners. Multivariate analysis showed that both disclosure of ones HIV status to someone and to their male partners was significantly associated with increase in antiretroviral therapy (ART) adherence, the known HIV positive status of their partner, and male involvement during pregnancy. Participants who were diagnosed HIV positive during this current pregnancy were less likely to disclose their HIV status to someone. Non-disclosure during current pregnancy highlights a need for interventions that will encourage disclosure among HIV positive women, with a particular focus on those who are newly diagnosed. The findings also need to integrate male partner involvement and partner disclosure during pregnancy.